Raportowanie społecznej odpowiedzialności w świetle teorii i praktyki konkurencyjności przedsiębiorstwa - Raszkowska, Paulina (Corporate Social Responsibility Reporting under the Theory and Practice of Competitiveness, 2011)
Corporate Social Responsibility reporting is still new in Poland. Information about environment and social performance is usually published either in separate CSR reports or in annual reports (within the m anagem ent commentary' to the financial statement). This allows the author to undertake the first, introductory empirical analysis if the level of CSR reporting is correlated with the competitive position of a publishing economic unit.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2011; Nr 156, s. 298-309
Keywords: połeczna odpowiedzialność przedsiębiorstw; raportowanie społecznej odpowiedzialności przedsiębiorstwa; konkurencyjność